Thuringiensin: A Thermostable Secondary Metabolite from Bacillus thuringiensis with Insecticidal Activity against a Wide Range of Insects - Liu, Xiaoyan (MDPI, 2014)
Thuringiensin (Thu), also known as β-exotoxin, is a thermostable secondary metabolite secreted by Bacillus thuringiensis. It has insecticidal activity against a wide range of insects, including species belonging to the orders Diptera, Coleoptera, Lepidoptera, Hymenoptera, Orthoptera, and Isoptera, and several nematode species. The chemical formula of Thu is C(22)H(32)O(19)N(5)P, and it is composed of adenosine, glucose, phosphoric acid, and gluconic diacid. In contrast to the more frequently studied insecticidal crystal protein, Thu is not a protein but a small molecule oligosaccharide. In this review, a detailed and updated description of the characteristics, structure, insecticidal mechanism, separation and purification technology, and genetic determinants of Thu is provided.